2002
DOI: 10.1023/a:1021165830511
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Article (refereed)Mulatya

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thus data sets for individual species over time are not abundant, the sample sizes per age class where these data exist are generally small or limited to one age class only (e.g. Danjon et al 1999;Mulatya et al 2002;Docker and Hubble 2008), and thus the statistical power of many relationships are generally limited by small sample sizes. Nevertheless, such data, be they from replicated trials or from single tree observations, are necessary to both improve our general understanding of a species' performance and to develop, calibrate, and validate either conceptual or quantitative models that incorporate root information for use in predicting the effects of vegetation on slope stability (Ekanayake & Phillips 1999, 2002Schwarz et al 2010;Phillips et al 2011;Stokes et al 2014) and hence the effectiveness of revegetation policies (Phillips et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus data sets for individual species over time are not abundant, the sample sizes per age class where these data exist are generally small or limited to one age class only (e.g. Danjon et al 1999;Mulatya et al 2002;Docker and Hubble 2008), and thus the statistical power of many relationships are generally limited by small sample sizes. Nevertheless, such data, be they from replicated trials or from single tree observations, are necessary to both improve our general understanding of a species' performance and to develop, calibrate, and validate either conceptual or quantitative models that incorporate root information for use in predicting the effects of vegetation on slope stability (Ekanayake & Phillips 1999, 2002Schwarz et al 2010;Phillips et al 2011;Stokes et al 2014) and hence the effectiveness of revegetation policies (Phillips et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…When grafting tomato ( Solanum lycopersicum L.), eggplant ( Solanum melongena L.), and bell pepper ( Capsicum annuum L.) plants, seedlings are used as rootstocks and scions, and it is important that they are healthy and uniform in size at the time of grafting [ 29 , 30 , 31 ]. Studies have shown that the method of propagation influences root architecture, with stem cuttings developing shallower roots compared to seedlings [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melia volkensii Gürke (Mukau) is native to the arid and semi-arid savannah of Kenya, Tanzania, and Somalia [1]. The tree grows rapidly and is compatible with agroforestry [2,3]. Mukau leaves, bark, and fruit pulp are fodder [4].…”
Section: Introductionmentioning
confidence: 99%
“…Leaf and fruit extracts are used as insect repellants [8,9]. The tree is termite resistant [2,8,10] and produces hard timber, comparable to mahogany [11,12]. Pruned branches provide farmers with good firewood [2].…”
Section: Introductionmentioning
confidence: 99%